PENGEMBANGAN BAHAN AJAR PAI INTERAKTIF BERBASIS WEBSITE UNTUK MENINGKATKAN EFEKTIVITAS PEMBELAJARAN DI MTsS IHYAUSSUNNAH - Maghfirah, Lailatul (Journal of Contemporary Indonesian Islam, 2025)
The advancement of digital technology has driven innovation in education, including the creation of website-based interactive teaching materials. Such media allow the integration of text, images, audio, video, and animations, as well as interactive features like quizzes and discussions, enhancing accessibility, flexibility, and student engagement. This approach supports independent and collaborative learning while fostering digital literacy in line with the Merdeka Curriculum. This study focuses on developing interactive website-based Islamic Religious Education (PAI) materials at MTsS Ihyaussunnah using the ADDIE R&D model (Analysis, Design, Development, Implementation, Evaluation). The platform contains complete PAI content with interactive media and was implemented for class VIII students, accompanied by teacher training. Evaluation through tests, observations, and questionnaires indicated improved motivation, participation, and learning outcomes, while teachers found the materials effective and practical. Therefore, website-based PAI teaching resources are proven effective and recommended for broader adoption.